Designing And Implementing Effective CSR At Reflexite. - Huddlestone, Andrew (2006)
This research sets out to evaluate current Corporate Social Responsibility practices at Reflexite, with the objective of creating a methodology to improve adoption and implementation of future policies. New insights were uncovered through desk based research of theoretical models and frameworks, aligned with industry level investigation at the organizational and governmental levels. An employee questionnaire, accompanied by interviews with other key stakeholder groups, investigating their understanding, desire and practices of CSR, was incorporated into my evaluations. This primary research has given new insights into this evolving subject, and coupled with research into global best preactice, will enable me to present recommendations to the organization. The research concludes with four proposals, that will be presented to the Reflexite Board of Directors, outlining the theoretical and practical arguements for implementing new, innovative programmes, all of which are aligned within the strategic intent of our organization. This work will enable Reflexite's senior management to set a framework on which the corporation can improve existing social responsibility processes and proceedures, support environmental sustainability, and add measurable financial value to the economic performance of the business.